Klambi Lurik Compang-Camping: Sebuah Komposisi Karawitan - SUHARDJONO - (Institut Seni Indonesia Yogyakarta, 2009)
Klambi Lurik Compang-Camping Karawitan Composition. This article discusses the creation process ofKlambi Lurik Compang Camping karawitan composition. This composition is inspired by Jineman Klambi Lurik,penned by Wasiran –a traditional artist and teaching staff in Karawitan study programme in ISI Yogyakarta. Thisjineman is favoured by both laypeople and karawitan traditional artists. This composition consists of eight parts,united as one full composition. The creation methods are exploration, improvisation, and shaping.